2016
DOI: 10.1021/acs.langmuir.6b02219
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Modeling of Flavonoid–Biomembrane Interactions

Abstract: and visualization of the surface with BAM revealed a pronounced monolayer stabilization effect 10 with both quercetin and tiliroside, whereas rutin disrupted the monolayer structure rendering the 11 surface entirely smooth. SAXS showed a monotonous membrane thinning for all compounds 12 studied associated with an increase in the root mean square fluctuations of the membrane. Rutin, 13 quercetin and tiliroside decreased the bilayer thickness of DOPC by ~0.45 Å, 0.8 Å, and 1.1 Å at 14 6 mol %, respectively. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 66 publications
3
48
0
1
Order By: Relevance
“…Our hypothesis is also supported by lower proton leak across the IMM and an overall decrease in DCF fluorescence, albeit the latter is not exclusively indicative of ROS alone nor informative of specific ROS species formed [73], but limitations in this assay are outweighed by the highly significant differences observed in cells treated with quercetin and is the decrease is associated with the general change in redox status and lower oxidative stress. Previous studies have shown that quercetin improves mitochondrial bioenergetics in various other models [22,23], while a role in maintaining membrane integrity has also been hypothesized [74][75][76]. The lower Leak in high glucosetreated cells with quercetin led to enhanced mitochondrial respiration by maximizing coupling efficiency and was reflected in higher Routine and net ETS respiration, indicative of increased use of ETS capacity for ATP turnover [54] as found here.…”
Section: Discussionsupporting
confidence: 72%
“…Our hypothesis is also supported by lower proton leak across the IMM and an overall decrease in DCF fluorescence, albeit the latter is not exclusively indicative of ROS alone nor informative of specific ROS species formed [73], but limitations in this assay are outweighed by the highly significant differences observed in cells treated with quercetin and is the decrease is associated with the general change in redox status and lower oxidative stress. Previous studies have shown that quercetin improves mitochondrial bioenergetics in various other models [22,23], while a role in maintaining membrane integrity has also been hypothesized [74][75][76]. The lower Leak in high glucosetreated cells with quercetin led to enhanced mitochondrial respiration by maximizing coupling efficiency and was reflected in higher Routine and net ETS respiration, indicative of increased use of ETS capacity for ATP turnover [54] as found here.…”
Section: Discussionsupporting
confidence: 72%
“…Flavonoids are hydroxylated phenolic substances which are also able to complex with bacterial cell walls and disrupt microbial membranes [75,105]. Highly active flavonoids, quercetin (1), rutin (2), naringenin (3), sophoraflavanone (4), tiliroside (5) and 2, 4, 6trihydroxy-30-methyl chalcone (6) ( Figure 2) decreased lipid bilayer thickness and fluidity levels and increased membrane permeability, supporting the leaking of intracellular protein and ions in S. aureus and S. mutans [112,113]. These compounds contribute to the synergistic effect with ampicillin and tetracycline [114].…”
Section: Promote Cell Wall Disruption and Lysismentioning
confidence: 84%
“…The inhibitory effects of gallotannins may be attributed to their iron-complexing properties and ability to interact with proteins and inhibit enzyme activities [79]. At the same time, flavonoids have a series of antibacterial actions with different mechanisms of action, such as inhibition of nucleic acid synthesis [80], induction of cytoplasmic membrane damage [81,82] and inhibition of energy metabolism [83], biofilm formation [3] and bacterial toxin production [84]. The flavonoid catechin can penetrate the lipid bilayers of the membrane resulting in leakage of intramembranous materials and liposome aggregation [85,86].…”
Section: Foodborne Pathogens and Food Spoilage Organismsmentioning
confidence: 99%